2018
DOI: 10.5815/ijcnis.2018.09.04
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of Steganography Techniques

Abstract: Confidentiality calls for substantial research and development in network security and data communication. Several techniques have been proposed for the past decades to ensure secure and confidential transmission of data. Steganography is a significant method of hiding data in another media, such that it is physically and virtually invisible. It is used primarily to ensure secure communication in an indiscernible fashion so that the hidden information is not discovered at any stage. The goal is to hide the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The convergence of the development parameters of countries of different levels of development is possible as a result of the co-evolution of the economic systems of these countries, their participation in the implementation of effective production, innovation and logistics projects. To this end, countries with economies in transition must maintain technological compatibility with developed countries in specific sectors of the respective region of the world [16][17][18].…”
Section: Results Of the Studymentioning
confidence: 99%
“…The convergence of the development parameters of countries of different levels of development is possible as a result of the co-evolution of the economic systems of these countries, their participation in the implementation of effective production, innovation and logistics projects. To this end, countries with economies in transition must maintain technological compatibility with developed countries in specific sectors of the respective region of the world [16][17][18].…”
Section: Results Of the Studymentioning
confidence: 99%
“…On the other hand, Sharma et al [17] presented a number of research and evaluation results of the effectiveness and safety of BPCS and LSB techniques. The research results showed that in the BPCS technique, all the data was embedded in a complex noisy blue plane.…”
Section: A Bpcs Technique and Some Improvementsmentioning
confidence: 99%
“…In addition to the Wavelet Motion Analyzer, the algorithms are also compared using Sample Pair Analysis [25] and Peak Signal Noise Ratio (PSNR) [3].…”
Section: Training and Testingmentioning
confidence: 99%
“…Despite this, increasingly sophisticated and oblique attack vectors have been developed to bypass cryptographic solutions. In addition, data breaches are a matter of concern, making it preferable that even stored data is not recognized as such [2,3]. As such, it has become increasingly worthwhile to combine encryption with data hiding, further enhancing security via data confidentiality [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation